Inverse heat problem of determining unknown surface heat flux in a molten salt loop. (August 2019) - Fernández-Torrijos, M.; Sobrino, C.; Almendros-Ibáñez, J.A.; Marugán-Cruz, C.; Santana, D.
Graphical abstract: Highlights: A molten salt loop that simulates a tube of a solar tower receiver is presented. The tube conducting molten salt receives a high nonuniform heat flux provided by an induction heater. The surface temperature and the deflection of the tube under solar power tower operating conditions are measured. An inverse problem is applied to accurately obtain the heat flux reaching the tube. The measurement of the deflection of the tube is used to verify the inverse problem. Abstract: Inverse heat transfer problems typically rely on temperature measurements for estimating unknown boundary heat flux, such as that in the water tubes of steam boilers or central receivers in solar tower power plants. In this work, an experimental facility consisting of a molten salt loop that simulates a tube of a solar tower receiver is presented to obtain the outer tube surface temperatures under solar tower power plant operating conditions. The external surface f the pipe in the test section is heated in a controlled manner with an induction heater, which provides a very high nonuniform heat flux. An inverse thermal method has been applied to obtain the incident heat flux onto the receiver tube from the outer surface temperature measurements. To solve the inverse problem, a transient two-dimensional numerical model of a circular pipe flowing molten nitrate salt and subjected to a nonhomogeneous circumferential heat flux has been developed. The heat flux calculation with the inverse method is in accordance with the heat flux estimation based on the calibration of the induction heater. A good agreement between the experimental and calculated temperatures is observed. Furthermore, the deflection of the tube caused by the nonhomogeneous heat flux is measured and is compared to the deflection calculated from the radial temperature profile from the inverse problem solution, and a good agreement between both results is observed.